EDUKASI KUALITAS AIR BERSIH DENGAN PENENTUAN ZAT ORGANIK SEBAGAI UPAYA PENCEGAHAN STUNTING DI SMK BHAKTI KENCANA CIMAHI - rismiarti, zuri; Rohayati, Rohayati (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2025)
Stunting itself is a condition of failure to thrive in children (body and brain growth) due to long-term malnutrition. This disorder is characterized by a child's height being stunted or much shorter than their peers. In addition to the lack of nutritional intake in food, it turns out that stunting can be influenced by the adequacy and safety of drinking water and sanitation. According to WHO, the provision of safe drinking water and sanitation determines human life and life. These two basic needs can reduce the disease index by 0.39%. Without safe water and sanitation, children become vulnerable to stunting. Clean water that meets health requirements must be safe in terms of physical, chemical, microbiological and radioactivity. Most people living in urban areas do not use clean water from the Regional Drinking Water Company (PDAM), but to get clean water, people try to make dug wells or drilled wells for their daily needs. In terms of quantity, this can be met, but in terms of quality, this is less noticed by the community. From the results of observations in the field, yellow water was seen from several residents' houses. The cause of the yellow water is the presence of iron (Fe) and organic materials (KMnO4). In this activity, participants who can participate are active students. The selection of students as the target community in this activity is based on considerations of their social roles in society. Students, in their functions and roles in society are agents of change, social control, strong future generations (iron stock), and role models (moral force). Based on these functions and roles, it is hoped that after participating in this educational activity, students will be able to become guardians, reminders and mouthpieces for the information presented in this educational activity to the community so that they can prevent stunting.